Exploring Applied Strategies for English-Language Dubbing - Spiteri Miggiani, Giselle (Journal of Audiovisual Translation, 2021)
The sudden boom of non-English language content on popular streaming platforms has obliged media localisation companies to react and adapt quickly to provide the market with English dubbing lip-synch services. This comes with several challenges due to the absence of a long-established English dubbing tradition and professional practice, as well as the lack of consolidated norms and conventions, or a textual repertoire to act as a point of reference. This paper builds on a prior theoretical study (Spiteri Miggiani, 2021) that seeks to identify potential norms as well as challenges in English-language dubbing. It goes a step further by exploring strategies and techniques that could address the identified challenges while aiming to satisfy the generally accepted quality standards that govern dubbing globally. The proposed strategies apply to the dubbing workflow as a whole with a special focus on the dubbing text adaptation process. The study aims to set the grounds for further research required to corroborate these strategies through applied studies in an academic setting, or through collaboration with localisation companies where they can be tested and observed in professional practice. Lay Summary We are currently experiencing a boom in films and TV series in a variety of languages other than English, mostly thanks to the popularity of streaming platforms such as Netflix and Amazon Prime Video. These productions need to be subtitled and dubbed into English. Dubbing in English is not a consolidated tradition and therefore it lacks its own set of patterns. To this end, I have already conducted a study to try to pinpoint the main challenges of English language dubbing and the patterns that have emerged so far. This enables me to take a step further, especially since it seems that viewers do not always react positively to dubbed content in English. This not-so-favourable response may also depend on the fact that they are not accustomed to dubbing. Having already identified some of the challenges related to lip-synching, rhythmic synchrony, natural sounding language, intonation, sound mixing, voice variety, and so on, in this paper, I propose practical strategies that can possibly help to deal with such issues. The main goal is to explore ways and means to enhance quality, especially in the translation and adaptation of these works. The ultimate aim is to obtain a credible product that engages the viewers and encourages them to binge on the next episode. We want the audience to forget or lose awareness of the fact that they are listening to newly recorded voices and a new target language.